Dampak Pembangunan Jalan Tol Bali Mandara terhadap Aktivitas Wisata di Ekowisata Kampoeng Kepiting, Tuban Bali - Mastari, Kadek; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA, 2020)
Tourism is a very reliable sector in this globalization era. Indonesia is one country that relies heavily on the tourism sector. Bali is one of the provinces in Indonesia. Over time, Bali tourism continues to grow even better. This development can be seen from the development that has been carried out in Bali, such as infrastructure development. One of the infrastructures that has been created is Jalan Toi Bali Mandara I Gusti Ngurah Rai, located in Badung Regency. The purpose of this study is to determine the impact of the construction of the Bali Mandara Toll Road on tourist activities in the Kampoeng Kepan Ecotourism attraction in Tuban Bali. The type of data in this study uses qualitative data. And data sources in this study are primary data sources and qualitative data sources. Data collection in this study uses observation techniques, interviews and documentation For the determination of informants through puposive sampling Data analysis techniques used are qualitative descriptive data analysis techniques The results in this study are the impacts caused in the construction of the Bali Mandara toll road on tourist activities that have an impact very good, a lot of new innovations that can be used as tourist activities, then after the construction is finished tourism activities can run well and normal, the construction of toll roads is very supportive to attract tourists in tourism activities The construction of the Bali Mandara Toll Road has a good impact on tourism activities in Kampoeng Crab Ecotouris. Keywords: impact, development, tourist activity, and ecotourism kampoeng kepiting